Investigating muscle regeneration with a dermis/small intestinal submucosa scaffold in a rat full‐thickness abdominal wall defect model. Issue 2 (29th May 2014) - Ma, Jinjin; Sahoo, Sambit; Baker, Andrew R.; Derwin, Kathleen A.
Abstract Repair of large complex ventral wall hernias is challenging and outcomes are often poor due to hernia recurrence and compromised abdominal wall function. Currently, biological grafts are used to assist in repairing these complex hernias. Dermis grafts are often chosen because of their mechanical characteristics; however, dermis does not have the ability to promote the muscle regeneration needed to regain abdominal wall function. In contrast, small intestinal submucosa (SIS) grafts have been shown to promote muscle generation in volumetric muscle loss (VML) models. Hence, the objective of this study is to investigate the extent to which SIS grafts can be used together with dermis grafts to repair and promote muscle regeneration in a full‐thickness abdominal wall defect in a rat model. The dermis layer is intended to mechanically bridge the defect and support constructive tissue remodeling while the SIS is intended to degrade and promote neo‐muscle formation. After 16 weeks of implantation, we found only a small amount of vascularized muscle (<10% of the defect area) in the repaired defects. No significant difference in defect muscle area was found between the groups receiving the dermis + SIS scaffolds and the control (dermis alone) group. Our findings indicate that the SIS constructions investigated could not promote appreciable muscle regeneration in this rigorous animal model of VML and incomplete abdominal closure. Future investigation into combination scaffold, cell and molecular therapies would be warranted to address the need for functional muscle regeneration in challenging clinical conditions such as complex abdominal wall repair. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 355–364, 2015.